Application of the wellbeing theory on air traffic controllers: a model on how to flourish in practice at the workplace - Mohamed Tharikh, Shafazawana; Hamzah, Siti Raba'ah (Human Resource Management Academic Research Society, 2020)
Wellbeing is a persistent scope of positive feelings and subjective life assessments for each person which generally utilized conversely with bliss. People react differently to similar conditions, and they assess conditions subject to their unique wants, moral, culture and past experiences. Supporting and empowering wellbeing has the ability of benefiting both the employees and the organization. The wellbeing of employees is basic for the endurance and improvement of organizations worldwide. Wellbeing at work requires basic needs to be met and improved by conditions that incorporate supportive personal relationships, community empowerment, healthy and alluring environment. In Wellbeing Theory (WBT), there are five pillars which known as PERMA (P-positive emotion, E- engagement, R- relationship, M- meaning and A-achievement). Each one of the pillars is not clinical as it gives escalation to a higher-order construct of wellbeing that should then expect flourishing of everyone at the workplace.